A practical resource for negotiating the world of friendships and relationships - Bates, Liz (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This is a practical resource for use by teachers, support staff, and therapists that contains session ideas for use with children to promote kindness, friendship and self-compassion. It includes detailed lesson plans with extensive guidance and photocopiable activity sheets to support individuals, groups or classes of children aged from 6 - 11 years of age. This guidebook can be used to: Help children understand the value of kindness, both to themselves and to others Nurture the moral development of children Support children who may be struggling with self-worth and self-kindness This guidebook is available to purchase as part of a two-component set, Negotiating the World of Friendships and Relationships: A 'Cool to be Kind' Storybook and Practical Resource, that can be used by teachers, support staff and therapists to teach and promote kindness to primary aged children"--
Introduction Session 1 Cool Session 2 Coco and Kez Session 3 Otto and Indra Session 4 Ollie and Nina Session 5 Ling and Danny Session 6 Cool to be Kind Self Kindness Appendices 1 -- Super-powers 2 -- Feelings 3 -- How might it feel? 4 -- Calm 5 -- My Map of Me 6 -- Thoughts 7 -- Send a Cool to be Kind Message 8 -- Like / Not Like Continuum Cards 9 -- Cool to be Kind Cards 10 -- Kind to Me Cards
OCLC-licensed vendor bibliographic record.
Keywords: Friendship in children -- Juvenile literature; Kindness -- Juvenile literature; Interpersonal relations in children -- Juvenile literature; EDUCATION / General